The forwards of chaos: the Saramaguian double as a representation of the crisis of the Portuguese post-modern subject - Papke, Isabela Padilha (Revista Desassossego, 2022)
The present work aims to analyze the work, O Homem Duplicado (2002), by José Saramago, through a sociological perspective of literature. It is intended to reflect how the work, through the phenomenon of the double, established in the daily life of the protagonist character, outlines an allegory of the identity crisis of the Portuguese subject, in the postmodern world and in the capitalist system. In order to understand the notions of subjects' identities and their fragmentation, in modern and post-modern contexts, we are guided by theories such as those of Hall (2006). Theories such as Harvey (2006) and Han (2015) were also used in order to establish a political, historical and economic panorama of these contexts. Finally, we focus on the theories proposed by Souza Santos (1994) in order to understand how the Portuguese postmodern context interferes in the production, theme and plot, of the selected work, showing how the country in which the work had been produced, having complex relationships with postmodernity, outlines elucidative and fruitful interpretive possibilities of the issues addressed in its constitution, as well as Saramago's relationships with writing and Literature, in order to open up the intrinsic relationships of literature with context socio-historical to which it belongs